Diquat associated with copper sources for algae control: Efficacy and ecotoxicology - Garlich, Nathalia [UNESP]; Da Cruz, Claudinei; Da Silva, Adilson F. [UNESP]; Carraschi, Silvia P.; Malaspina, Igor C. [UNESP]; Pitelli, Robinson A. [UNESP]; Bianco, Silvano [UNESP] (Taylor & Francis Inc, 2016)
ABSTARCTThe aims of this research were to evaluate the efficacy of copper oxychloride (CuCl2.3Cu(OH)(2)), copper hydroxide (Cu(OH)(2)) and diquat (1.1-ethylene-2.2-bipyridyldiylium dibromide), isolated and in association with 0.1% of both copper sources, in the control of the unicellular algae Ankistrodesmus gracilis and the filamentous algae Pithophora kewesis, and to determine the acute toxicity of the tested chemicals in Hyphressobrycon eques, Pomacea canaliculata, Lemna minor and Azolla caroliniana. The efficacy was estimated by the methods of chlorophyll a and pheophytin a readings, changed into growth inhibition percentage. Both algae were exposed to the following concentrations: 0.2; 0.4; 0.8; 1.2mg L-1 of diquat and its association with the copper sources; and 0.1; 0.3; 0.5; 0.7; 1.0 and 1.5mg L-1 in the isolated applications of copper hydroxide and copper oxychloride. An untreated control was kept. The acute toxicity was estimatedby 50% lethal concentration (LC50). The copper sources were effective for A. gracilis control, at rates as high as 0.1mg L-1 (>95% efficacy). Isolated diquat and its association with copper hydroxide were both effective at rates as high as 0.4mg L-1, with 95 and 88% control efficacy, respectively. The copper oxychloride was effective at 0.2mg L-1, with 93% efficacy. None of the tested chemicals and associations was effective on P. kewesis control. The most sensitive non target organism to the tested chemicals was L. minor; the less sensitive was H. eques.
Keywords: Algaecide; chemical substances; environmental assessment; secondary effect